2022
DOI: 10.3390/antibiotics11111577
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Bacterial Prevalence and Antibiotic Resistance Patterns in the Acute Exacerbation of Chronic Obstructive Pulmonary Disease in Hospitalized Patients in South India

Abstract: Exacerbation due to antimicrobial-drug-resistant bacteria among chronic obstructive pulmonary disease (AECOPD) patients contributes to mortality and morbidity. We examined the prevalence of the bacterial organisms and trends in drug resistance in AECOPD. In this retrospective study, between January 2016 to December 2020, among 3027 AECOPD patients, 432 (14.3%) had bacteria isolated. The regression and generalized estimating equations (GEE) were used for trends in the resistance patterns over five years, adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…These factors signi cantly in uenced antibiotic resistance rates. Once more, our results align with the research, providing additional support to our conclusions (34).In children with bloodstream infections, Table 9 presents the antibiotic resistance patterns of E. coli. Ampicillin had the highest resistance rate at 66.7%, followed by cefotaxime at 55.6% (32).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These factors signi cantly in uenced antibiotic resistance rates. Once more, our results align with the research, providing additional support to our conclusions (34).In children with bloodstream infections, Table 9 presents the antibiotic resistance patterns of E. coli. Ampicillin had the highest resistance rate at 66.7%, followed by cefotaxime at 55.6% (32).…”
Section: Discussionsupporting
confidence: 88%
“…Our results nd validation in the study conducted by Rodriguez et al, which reported comparable resistance rates for E. coli in bloodstream infections in children, bolstering the credibility of our ndings (33). Conducting a logistic regression analysis for bloodstream infections in children (Table 10), we identi ed signi cant associations between antibiotic resistance and age, admission to the ICU, duration of hospital stays, and the use of a central line (34). These factors signi cantly in uenced antibiotic resistance rates.…”
Section: Discussionsupporting
confidence: 77%
“…, 2021 ). A study in South India has found that women had 2.89 higher odds of death compared with men, in cases of chronic obstructive pulmonary disease (often caused by exposure to noxious particles or gases), exacerbated by antimicrobial drug-resistant bacteria ( Kaleem Ullah et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…MDR bacteria are commonly identified in patients with chronic obstructive pulmonary disease (COPD) who experience severe acute exacerbations that require intubation and mechanical ventilation [ 27 , 28 ]. A study reported MDR infection caused higher mortality rate than drug-sensitive patients in COPD exacerbation (12%, vs. 4.7%) [ 29 ]. The effects of MDR bacterial infection on the clinical outcomes of patients with bronchiectasis require further clarification.…”
Section: Discussionmentioning
confidence: 99%